Enhancing public service delivery system through e-procurement the case of DTI - Soriano, Victorino S. (2003)
To perform its tasks, governments need to acquire goods and services. Public procurement gives substance to the tasks of government. Supplies, materials and equipment are major inputs in the discharge of basic governmental functions and services as well as in the conduct and management of development programs and projects.The Philippine public procurement is a multi-billion peso operation. Proper management of public procurement, therefore,is very important if government were to maximize access to its services by all citizens, within the context of fiscal constraints and the fulfillment of competing needs. Lack of transparency and competition, collusion, political interference, delays, and excessive use of discretionary criteria that lead to graft and corruption characterize procurement practices in the country. This sums up the three major issues in Philippine public procurement--lack of standard procedures, massive corruption and lack of governance. Promoting good governance, particularly in public procurement, will significantly reduce corruption and help government attain its development goals. Good governance or sound development management is the missing link in the poverty reduction efforts of many developing countries.The advent of Information and Communication Technology (ICT) as a highly leveraged enabling tool for delivery of services in the public and the private sector has by now been universally recognized. In public administration, the use of ICT on government operations has given rise to what is now termed as electronic governance, or simply e-governance. It is the application of ICT to the processes of government functions to bring about: Simple, Moral Accountable, Responsive and Transparent Governance. One are where government can fully take advantage of the benefits of ICT and promote good governance, the Philippine Government has underscored the use of ICT, specifically the Internet, in the procurement reform agenda. Article III, Section 8 of Republic Act (R.A.) 9184, better known as the Government Procurement Reform Act, provides for the use of electronic means in government procurement to promote transparency and efficiency. Accordingly, there shall be a single portal, that is, the Government Electronic Procurement System (G-EPS), that shall serve as the primary source of information on all government procurement.The opportunity to reduce the costs incurred in public procurement and use the savings in other worthwhile project is critically important to countries like the Philippines whose budget deficit has been a perennial problem. The cost reduction potential of e-procurement is derived from several economic factors--lower information costs, lower transaction costs, increased competition, and better specialization. Clearly, there are benefits that can be derived from bringing the government procurement process online. On the other hand, there are also issues that need to be addressed to ensure successful implementation and attain desired results. Resistance to change is one such obstacle. Government agencies are concerned that they would lose control of their procurement authority and that major changes would be made to their procurement process.Moreover, there are security issue in e-commerce that also need to be addressed so that it will increase the user's confidence on employing the technology. Among these security issues include authenticity, integrity, confidentiality and non-repudiation. The increasing e-environment demands that public organizations change the traditional ways of providing public services and administering their internal processes. One way of managing this change is by providing staff training.Utilizing e-procurement may prove to be costly but the benefits it will accrue to the agency, and especially to the public, will surely compensate for whatever cost it may incur. Improving procurement through the use of ICT is the key to delivering better services.